Monitoring strategy of supervisory system of a steam distribution network by establishing qualification techniques of two-phase flow - Szakonyi, Lajos; Sári, Zoltán; Jancskárné Anweiler, Ildikó (Acta Agraria Kaposváriensis, 2010)
Devices traditionally operated in regional steam networks are neither able to determine the liquid content of the flowing medium nor the velocity distribution and volume fraction of the phases having incidentally different velocities at the consumers’ end of the network. The established supervisory system providing intelligent monitoring enables to address these problems. Besides the traditional measurement units required for the operation of the supervisory system, it is crucial to build special measuring devices (in order to obtain information about velocity distribution and the volume occupation of the phases in two phase flow, and to measure the condensate flow toward the environment) with unique design as well, and the mobile communication based transfer of measurement data to the central computers of the supervisory system is also needed. The developed monitoring strategy enables the on-line determination of the correct mass- and energy balance during the process.
Keywords: two-phase flow; identification; process control